The Effect of Income, and Lifestyle to the Boarding Student (Kos) Consumption during the Pandemic Covid-19 at the Faculty of Economics and Business, Palangka Raya University - Magdalena, Suryani; Elia, Andrie; Irawan, Irawan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research aim to the effect of income and lifestyle to the bourding student (kos) comsumption. This research uses a quantitative approach with multiple linear regression of the analysis method, with income and lifestyle as independent variables, and consumption as the dependent variable. Primary data obtained from student respondents with a questionnaire. The results of this reseach indicate that the partial (test-t), income has a significant effect on student consumption, lifestyle has a significant effect on student consumption. Likewise with the results of the simultaneous (test-F), that income and lifestyle have a significant effect on student consumption.